Laboratory Evaluation of A New Molluscicide Application Method - Gasmelseed Mohamed, Nagla; Abdalhamid Adeel, Ahmed Awad; Babiker, Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 4 عدد 2 (2008), 2008)
The paper reports an investigation, in the laboratory, of a new method for the application of the molluscicide, Niclosamide, using the concept of slow-release with local materials as matrices. The local matrices tested were the seeds of the mango and the cobs of the maize. The objective was to reduce the cost of the snail control operations. 1, 5 and 10 seeds and/or cobs were immersed into 4 concentrations (0.6, 1.0, 2.0 and 4.0 ppm) of Niclosamide for different hours (1, 2, 6, 12, 24 and 48 hrs). B. pfeifferi snails were then exposed to the immersed seeds and cobs for different hours (1, 2, 6, 24, 48 and 72 hours). Different statistical procedures were used to analyze the data. The mean time of mortality of B. pfeifferi snail indicated that the cobs of the maize were a superior matrix for Niclosamide than the seeds of the mango. The LC 50 and LC 95 indicated that the combination of 10 cobs immersed for 12 hours in 4.0 ppm was the effective combination to achieve high mortality rates among B. pfiefferi snails after 48 hours exposure. The method proved to be, in the laboratory, cost-effective in terms of the quantity of Niclosamide required to result in a high mortality among the snails.